Dermatofibrosarcoma protuberans in adolescence: a case report and literature review - Valiulytė, Agnietė; Gudavičiūtė, Milda; Trainavičius, Kęstutis; Šeinin, Dmitrij (Lietuvos chirurgija, 2015)
Dermatofibrosarcoma protuberans is a very rare malignant neoplasm in children. It is reported that the classic form of dermatofibrosarcoma has a very limited metastatic potential, while a fibrosarcomous transformation of dermatofibrosarcoma protuberans has a much higher potential. We present a case of a 17-year-old boy with a huge ulcerated mass (17 x 15 cm) on his right thigh. At operation, the pathological diagnosis was dermatofibrosarcoma protuberans with a fibrosarcomous component. All lesions were removed by surgical excision with a margin of 1.5 to 3 cm. After one year, there is no evidence of tumor recurrence.
Keywords: dermatofibrosarcoma protuberans in children; soft tissue sarcomas; fibrosarcomous transformation; surgical treatment